Performance of rapid diagnostic tests for imported malaria in clinical practice: results of a national multicenter study. - Sandrine Houzé; Isabelle Boutron; Anne Marmorat; Marie Dalichampt; Christophe Choquet; Isabelle Poilane; Nadine Godineau; Anne-Sophie Le Guern; Marc Thellier; Hélène Broutier; Odile Fenneteau; Pascal Millet; et al. (PLoS ONE, 2013)
We compared the performance of four rapid diagnostic tests (RDTs) for imported malaria, and particularly Plasmodium falciparum infection, using thick and thin blood smears as the gold standard. All the tests are designed to detect at least one protein specific to P. falciparum (Plasmodium histidine-rich protein 2 (PfHRP2) or Plasmodium LDH (PfLDH)) and one pan-Plasmodium protein (aldolase or Plasmodium LDH (pLDH)). 1,311 consecutive patients presenting to 9 French hospitals with suspected malaria were included in this prospective study between April 2006 and September 2008. Blood smears revealed malaria parasites in 374 cases (29%). For the diagnosis of P. falciparum infection, the three tests detecting PfHRP2 showed high and similar sensitivity (96%), positive predictive value (PPV) (90%) and negative predictive value (NPV) (98%). The PfLDH test showed lower sensitivity (83%) and NPV (80%), despite good PPV (98%). For the diagnosis of non-falciparum species, the PPV and NPV of tests targeting pLDH or aldolase were 94-99% and 52-64%, respectively. PfHRP2-based RDTs are thus an acceptable alternative to routine microscopy for diagnosing P. falciparum malaria. However, as malaria may be misdiagnosed with RDTs, all negative results must be confirmed by the reference diagnostic method when clinical, biological or other factors are highly suggestive of malaria.